Importance of Methane Oxidation for Microbial Degradation of the Herbicide Bentazone in Drinking Water Production - Hedegaard, Mathilde J.; Schliemann-Haug, Manuela A.; Milanovic, Nikola; Lee, Carson O.; Boe-Hansen, Rasmus; Albrechtsen, Hans-Jørgen (Frontiers in Environmental Science, 2020)
Bentazone is a herbicide, which is frequently detected in groundwater due to its mobility and persistence in aquifers. Groundwater is used as a drinking water source all over the world, and sustainable methods to remove pesticides at low concentrations are urgently needed since pesticide contaminations can adversely affect human health. The aim of this study was to investigate whether microbial bentazone degradation was associated with methane oxidation in full-scale drinking water treatment plants. To this end, we investigated bentazone biodegradation in microcosms with water and filter material from rapid sand filters, or biomass from aeration systems, and we investigated the statistical relation between the presence of methane and bentazone in groundwater abstraction wells. An array of evidence supported an association between bentazone degradation and methane oxidation in the biological treatment process. The biodegradation potential of bentazone was associated with the presence of methane in the raw water at 14 different water works. In contrast, no association was observed with any of the other investigated inorganic energy sources, e.g. ammonium. Addition of acetylene inhibited methane oxidation and the bentazone degradation in filter material from two investigated waterworks. Biomass from the aeration tanks degraded bentazone, but only while oxidizing methane. Bentazone removal rates and methane removal rates correlated significantly across all the experiments with biomass or filter material, with an overall transformation yield of 15×10-5 moleBTZ/moleCH4. This demonstrated that the bentazone degradation was conducted by the same type of process in all the investigated communities, governed by methane oxidation. Furthermore, based on more than 10.000 water analyses from waterworks abstraction wells in Denmark, bentazone was detected significantly less frequent in wells with high methane concentrations (> 1 mg/L) than in wells without methane. This suggests that biological treatment of bentazone contamination in drinking water may be achieved using methanotrophs.